Exploring the interplay of topic discussion, follower engagement, and crows funding performance: a mediation analysis - Dato Haji Yahya, Mohamed Hisham; Jie, Gao; Senik, Rosmila; Abdullah, Amalina (Scientific Research Publishing, 2024)
The aim of this paper is to investigate the mediating effect of the number of project followers and project discussions on the success of reward-based crowdfunding. In Internet product crowdfunding, sponsors usually use social media, including the product crowdfunding platform itself and third-party social media such as Weibo and WeChat. Product crowdfunding platforms, Weibo and WeChat attract different groups of people. The ultimate impact on product crowdfunding may also be different. In order to test the impact of social media on the fundraising level of Internet product crowdfunding projects, this chapter chooses JingDong (JD) crowdfunding platform as the research object. In addition, the number of people following crowdfunding projects and the number of topics discussed may have a mediating effect. With the help of “HouYi” data acquisition software, the daily dynamic data of each crowdfunding project was collected. The panel database of the crowdfunding process was formed by collecting the data of all 457 crowdfunding projects on the Modian crowdfunding platform within 3 months. OLS multiple regression analysis was used to detect the data of the influence of each independent variable on the dependent variable. The test shows that both the professional JD crowdfunding platform and the communication and promotion of third-party social media Weibo and WeChat can significantly exert a significant positive impact on the fundraising level of product crowdfunding projects, and this positive impact is achieved by influencing the number of followers and topic discussions of crowdfunding projects on JD crowdfunding platform. In other words, the number of followers and the number of topic discussions of crowdfunding projects have a significant mediating effect.